Implementasi Program Pendidikan Profesi Gurur Dalam Jabatan Bidang Studi Guru Kelas SD di Era Covid-19 - Syamsul Alam; M. Syarif Sumantri; Khaerudin Khaerudin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to identify the implementation of the In-service Teacher Professional Education (PPGDJ) program, especially in the field of study for elementary school teachers at Makassar State University (UNM) in the COVID-19 era. This research was carried out in April-July 2021 at the Makassar State University (UNM) Teacher Professional Education Study Program (Prodi). Subjects in this study included lecturers, civil servant teachers, and PPGDJ students for elementary school teachers. This study used a qualitative approach with case study design. Sources of data were obtained from program managers, supervisors, civil servants, PPGDJ students, elementary school teachers. The technique of collecting research data is through observation, interviews, and documentation studies. The data analysis technique used is descriptive qualitative analysis method. The results of the research. Implementation of the PPG In Position program in the field of study for elementary school teachers at UNM in the COVID-19 era was carried out well. It is proven by all stages of implementing the PPG program in the field of study for elementary school teachers at UNM that are well organized and structured. This increases the competence of teachers, both pedagogical competence, personality competence, social competence, and professional competence which gives birth to the expected professional teachers. The impact of the COVID-19 pandemic which forced PPG students in the field of study for elementary class teachers to be able to master Information and Communication Technology (ICT) in line with increasing teachers' IT abilities. So that teachers feel satisfied and optimistic in providing changes in learning in schools for the better. Keywords: Program Implementation, Teacher Education, COVID-19